PENERAPAN TEKNIK PEMBELAJARAN PROBING PROMPTING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 112 PEKANBARU - Yulianti, Eka; Alpusari, Mahmud; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the lack of science learning outcomes of students with an average grade 69.47. Forms of this research is the Classroom Action Research (CAR), which is consist of two cycles whose implementation started onFebruary 15 until March 5, 2016 with the subject amounted to 38 students consisting of 23 male students and 15 female students. This study aims to improve learning outcomes fifth grade science students at SDN 112 Pekanbaru through the application of learning probing prompting techniques, this study consisted of learning tools and data collection instruments. Data analysis technique used is the analysis of the activity of teachers and students and analysis of student learning outcomes. Analysis techinque of data on the activities of teachers and students is based on the observation sheet during the implementation of the action. While the data analysis of student learning outcomes demonstrate mastery of student learning outcomes. Based on the analysis of activity observation sheet teachers and students evidently the activities of teachers and students has increased at every meeting. Teachers activity with the application of learning techniques probing prompting at the first meeting is 57,14% (sufficient categories), and the second meeting of the first cycle is 75% (good categories). In the second cycle, the activity of teachers at the first meeting amounted to 85,71% (the excellent category), and the second meeting amounted to 96,43% (excellent category). Activities of students at the first meeting of the first cycle is 53,57% (sufficient category) and the secondmeeting of 78,57% (both categories). In the second cycle, the student activity at the first meeting is 85,71% (excellent category), the second meeting amounted to 92,86% (excellent category). Science learning outcomes of students before the application of learning techniques probing prompting has an average value of 69.47, after the application of learning techniques prompting probing average student learningoutcomes increase in daily tests (UH I) became 76,76 with a percentage increase of 10, 49% and at the second daily test (UH II) average student learning outcomes increased to 85,78 with the percentage increase of 23,48%. Based on this it can be concluded that the application of the probing prompting learning techniques could improve the learning outcomes fifth grade science students at SDN 112 Pekanbaru.Keywords: probing promptin techiques, science learning outcomes